Event structure metaphors through the body : translation from English to American Sign Language - Roush, Daniel R. (Figurative thought and language (FTL), 2018)
"How do the experiences of people who have different bodies (deaf versus hearing) shape their thoughts and metaphors? Do different linguistic modes of expression (signed versus spoken) have a shaping force as well? This book investigates the metaphorical production of culturally-Deaf translators who work from English to American Sign Language (ASL). It describes how Event Structure Metaphors are handled across languages of two different modalities. Through the use of corpus-based evidence, several specific questions are addressed: are the main branches of Event Structure Metaphors--the Location and Object branches--exhibited in ASL? Are these two branches adequate to explain the event-related linguistic metaphors identified in the translation corpus? To what extent do translators maintain, shift, add, and omit expressions of these metaphors? While answering these specific questions, this book makes a significant elaboration to the two-branch theory of Event Structure Metaphors. It raises larger questions of how bilinguals handle competing conceptualizations of events and contributes to emerging interest in how body specificity, linguistic modes, and cultural context affect metaphoric variability"--